Impact of Work Ethics on Quarter-Life Crisis Severity, Moderated by Perceived Social Support - Prisha Kapoor; Dr. Bhanu BS (International Journal of Indian Psychȯlogy, 2025)
Young adults (22–38) experience a Quarter-Life Crisis (QLC) due to career stress and identity struggles. This study examines the link between work ethics and QLC severity, considering the role of perceived social support. Using the Occupational Work Ethic Inventory (OWEI), Quarter-Life Crisis Scale (QLCS), and Multidimensional Scale of Perceived Social Support (MSPSS), findings revealed a moderate negative correlation between strong work ethics and severe QLC symptoms. Social support reinforced this relationship, as emotional and professional backing reduced workplace stress and existential concerns. However, work mode (remote, hybrid, onsite) had no significant effect. To enhance resilience in early career professionals, organizations must implement ethical leadership programs, professional mentoring, and employee welfare initiatives. These measures are crucial in mitigating QLC-related psychological distress and fostering a supportive work environment.